2018
DOI: 10.3389/fneur.2018.00061
|View full text |Cite
|
Sign up to set email alerts
|

Responsivity of Periaqueductal Gray Connectivity Is Related to Headache Frequency in Episodic Migraine

Abstract: Migraineurs show hypersensitivity to sensory stimuli at various stages throughout the migraine cycle. A number of putative processes have been implicated including a dysfunction in the descending pain modulatory system in which the periaqueductal gray (PAG) is considered to play a crucial role. Recurring migraine attacks could progressively perturb this system, lowering the threshold for future attacks, and contribute to disease chronification. Here, we investigated PAG connectivity with other brain regions du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 79 publications
(89 reference statements)
3
36
2
Order By: Relevance
“…Similarly, female migraine without aura patients have decreased functional connectivity among pain-related brain regions [ 181 ]. The connectivity of the PFC with the PAG is also decreased in patients with migraine compared to healthy individuals [ 182 ]. A study of the relationship between white matter changes and pain intensity and pain affect in elderly people shows that the presence of white matter changes is related to increased pain affect, but not with pain intensity [ 183 ].…”
Section: Changes In the Pfc During Chronic Painmentioning
confidence: 99%
“…Similarly, female migraine without aura patients have decreased functional connectivity among pain-related brain regions [ 181 ]. The connectivity of the PFC with the PAG is also decreased in patients with migraine compared to healthy individuals [ 182 ]. A study of the relationship between white matter changes and pain intensity and pain affect in elderly people shows that the presence of white matter changes is related to increased pain affect, but not with pain intensity [ 183 ].…”
Section: Changes In the Pfc During Chronic Painmentioning
confidence: 99%
“…These changes likely include aberrant functioning within descending painmodulation brainstem areas that render pain circuits more sensitive to ascending noxious signals (Raskin et al, 1987). For example, people with migraine show diminished resistance to experimental pain between headaches, which has been attributed to either reduced inhibition or enhanced facilitation from descending brainstem pain-modulation areas (e.g., PAG, RVM), effectively increasing susceptibility to migraine attacks (Solstrand Dahlberg et al, 2018). Additionally, the PAG-RVM pathway is thought to regulate secondary symptoms associated with migraine headaches (e.g., appetite changes, sedentary behavior, sleepiness, etc.…”
Section: Review Ofmentioning
confidence: 99%
“…Cortical and subcortical brain regions may provide additional pain modulation. For example, one recent fMRI investigation (Dahlberg et al, 2018) found reduced coupling between the PAG and prefrontal cortex, a cortical region with links to descending pain modulation (Wager et al, 2004), among inter-ictal migraine patients. Whether the transition from inter-ictal to pre-ictal to ictal represents a shift from cortical-PAG functional connectivity to PAG-RVM functional connectivity warrants additional consideration.…”
Section: Review Ofmentioning
confidence: 99%
“…Additionally, Solstrand Dahlberg and colleagues report findings that a decreased connectivity of regions in the brainstem that are involved in orofacial pain with parts of the descending pain modulation system is present in patients suffering from migraine. However, they also conclude that the exact anatomy of the trigeminal pathways in the human brainstem remain elusive (Solstrand Dahlberg et al 2018 ). In 2016, a review of tracing studies in animals and functional MRI studies in humans provided an overview of the trigeminal tracts in the brainstem (Henssen et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%